Integrasi Kurikulum Pondok Pesantren dalam Peningkatan Pemahaman Agama Islam di SMP IT Nurul Yaqin Kabupaten Sorong - Imron, Ali; Hamzah, Hamzah; Yudiawan, Agus (Al-Fikr: Jurnal Pendidikan Islam, 2017)
In this study, the authors aim to explore as deeply as possible how the process of integration of the boarding school curriculum in public school is. In addition, the authors aim to identify the components in the integration of the boarding school curriculum to public schools. Because this integration adds 7 religious subjects to the SMP IT, while in the school there is already a religious lesson but only the scope of PAI which teaches only the outline of the discussion. Meanwhile, after the Pondok curriculum had been included, there were many changes, especially in religious studies that were more detailed and the students can master it more efficient. In this study, the authors use qualitative research methods because of seeing the location of the study. Integration is the merging of an object against other objects to get a new indication. It is the merging between content in the Islamic Boarding School and content in SMP IT Nurul Yaqin. The contents inside are subjects that are included, regulations and assumptions related to the integration of Schools Based Boarding School.